Functional Relations Modulate the Responsiveness to Affordances Despite the Impact of Conflicting Stimulus–Response Mappings - Vastano, Roberta; Finn, Martin; Barnes-Holmes, Dermot (Frontiers in Psychology, 2017)
The study investigated how conflicting stimulus-response mappings influenced affordance processing given a manipulation of the functional relations. Participants performed a task involving consistent – inconsistent stimulus-response mappings: Implicit Relational Assessment Procedure (IRAP). They were instructed to confirm or to deny a relation between words and tool-objects (Consistent blocks) or to provide non-conventional responses (Inconsistent blocks). The relations between stimuli could functionally match (e.g. Kitchen-Spatula) or not (e.g. Kitchen-Hammer), as well as the spatial relations (e.g. a match or a mismatch between participants’ hand response and the tool-object orientation). The results showed faster RTs when functional relations between stimuli matched both in consistent and inconsistent blocks. Differences in RTs and accuracy between consistent and inconsistent blocks were only found when the functional relation between stimuli matched. No modulation of the performance was observed for mismatching functional relations and spatial relations between blocks. These results support the hypothesis that the responsiveness to affordances is strongly modulated by matching functional relations, despite the impact of conflicting stimulus-response mappings.